IDNLearn.com: Your destination for reliable and timely answers to any question. Ask your questions and receive comprehensive, trustworthy responses from our dedicated team of experts.

Please solve
(2x^2 +x+4) (x+7) = 6x^3+29x^2+47x+28
with explanation
ASAP!!!
On a time crunch!!!!!


Sagot :

Answer: x = 0

Step-by-step explanation:

Subtract 6x^3+29x^2+47x+28 from both sides:

(2^2 + x + 4) (x - 7) - 6x^3+29x^2+47x+28

(6x^3+29x^2+47x+28)-6x^3+29x^2+47x+28

= -4x^3 - 14x^2 - 36x = 0

Now factor the left side:

-4x^3 - 14x^2 - 36x = 0

(-2x) (2x^2 + 7x + 18) = 0

Now set the factors equal to 0

-2x = 0 or 2x^2 + 7x + 18 = 0

x = 0

Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. Thank you for visiting IDNLearn.com. We’re here to provide clear and concise answers, so visit us again soon.